Effect of Vitamin D3 Supplementation on Hepcidin and Ferritin Levels in Children with CKD - Rachmayani, Andi Muldiana Dwi; Aras, Jusli; Rauf, Syarifuddin; Lawang, Aizah (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2025)
Chronic Kidney Disease (CKD), as a worldwide health concern, results in several complications. Anemia caused by erythropoietin deficiency, reduced iron absorption, and abnormalities in vitamin D metabolism are frequently seen in children with CKD. Ferritin is the body's iron storage, whereas hepcidin is a protein that impacts iron metabolism. Low vitamin D levels exacerbate heme deficiency and anemia. This study aimed to know the effect of vitamin D3 supplementation on serum hepcidin and ferritin levels in children with CKD. A prospective cohort design was conducted in Dr. Wahidin Sudirohusodo Hospital from July 2023 to April 2024. Samples were divided into two groups based on GFR. Complete blood count, vitamin D, ferritin, and hepcidin level examinations were performed before and after supplementation. The data was analyzed with the Mann-Whitney test. Forty-three children between the ages of 2 and 18 were involved in this study. There was no significant difference in the groups' age, gender, nutritional status, or diagnosis (p > 0.05). Ferritin levels significantly dropped in group II (p=0.002), hepcidin levels significantly dropped in all subjects (p < 0.001), and vitamin D levels increased significantly in both groups (p < 0.001) following supplementation. Vitamin D supplementation effectively increases vitamin D levels in children with CKD and significantly affects ferritin and hepcidin levels.